The complete mitochondrial genome of the far Eastern myotis: Myotis bombinus Thomas, 1906 in mainland of Korea (Chiroptera, Vespertilionidae) - Kim, Byeori (Mitochondrial DNA B Resour, 2021)
We have determined the second mitochondrial genome of Myotis bombinus Thomas, 1906 in mainland of Korea. The circular mitogenome of M. bombinus is 17,035 bp long which is slightly shorter than that of the previous mitogenome of M. bombinus. It includes 13 protein-coding genes (PCGs), two ribosomal RNA genes, and 22 transfer RNAs. The base composition was AT-biased (66.1%). Fifty single nucleotide polymorphisms and 14 insertions were identified between two mitogenomes of M. bombinus. Phylogenetic trees show that both M. bominus mitogenomes are clustered in one clade.